FAKTOR FAKTOR PENYEBAB RENDAHNYA CAPAIAN DETEKSI DINI KANKER LEHER RAHIM METODE IVA PADA WUS 30 Sampai 50 TAHUN DI WILAYAH PUSKESMAS CISADEA - Surachmindari Surachmindari; Lisa Purbawaning Wulandari (Jurnal Pendidikan Kesehatan, 2021)
Cisadea Health Center has the lowest achievement of cervical cancer early detection in 2018 only 0.98 percent. Research purpose is identify the factors that cause the low achievement of cervical cancer early detection using IVA method. Design this research is descriptive quantitative, sampling using purposive sampling technique with a total sample 40 people. The instrument is questionnaire. The results showed that 56 percent of respondents had higher education level, 44 percent had good knowledge, 60 percent were economically disadvantaged, 52 percent received negative support and 80 percent had moderate interest. The interest factor has a higher tendency behind the low achievement of cervical cancer early detection